Association of the HTR2A 102T/C polymorphism with attempted suicide: a meta-analysis. (August 2015) - Wang, Jin-Yu; Jia, Cun-Xian; Lian, Ying; Sun, Shi-Hua; Lyu, Ming; Wu, Andrew
Abstract : An association between the serotonin 2A receptor (5-HT2A receptor) gene and suicidal behavior has been reported in many studies. However, no consistent conclusion has been reached. One potential reason for this is heterogeneity in the studies analyzed, which may have been caused by the selection of different types of cases and controls. In the present study, we pooled data from the previous published papers to clarify the association between HTR2A 102T/C and attempted suicide. All case–control studies written in English and published up until 20 November 2013 were selected. The history of suicide attempts and other relevant data were extracted. According to the findings of previous studies, the recessive model was used to evaluate the role of genotype in attempted suicide. We divided the patients into three groups on the basis of the history of suicide attempts and mental disorder. Genotype distribution of the suicide attempters was compared with normal controls and patients with mental disorder, respectively. There were no significant differences in 5-HT2A receptor 102T/C genotype distributions between those who attempted suicide and the normal controls, and the results were similar for the comparisons with mental disorder patient controls. When subgroup analysis of the types of mental disorder was carried out, all heterogeneity disappeared and effect sizes increased. A significant association was observed for the schizophrenia disorder subgroup (odds ratio=1.73; 95% confidence interval: 1.11–2.69). Our meta-analysis does not support the previously suggested association between HTR2A 102T/C and attempted suicide in the general population. However, in patients with schizophrenia, the C/C genotype of 5-HT2A receptor 102T/C may increase the risk of attempted suicide. The heterogeneity in relevant studies may have been caused by the characteristic variety of mixed mental disorders.